Typology of indoor plants decoration in commercial buildings around Kuala Lumpur - Mohd Ali, Nor Asyiah; Hj. Baharuddin, Zainul Mukrim (2016)
Plants and vegetation were basically a very strong elements of nature that could bring a lot of functions and benefits to human and even to animals in term of physical and mental quality. As claimed by Beatly (2011), environment rich with nature and natural experiences will help in promoting another important values. This is the main reason why people have been bringing plants into their residential area or even into their houses in order to gain benefits and improving their indoor spaces environment. Since people nowadays are constructing more and more buildings such as offices, shopping malls and banks for their benefits or work in, unfortunately, there are less open spaces or area that they could enjoy nature and integrating with it. This resulted on the users stress level and health issues. The best way to solve the problem is by applying indoor landscape simultaneously could bringing life for indoor spaces as indoor plants could purify air and even help in reducing stress among workers or visitors of the building. Thus, the aim of this research is to provide the attractive and effective indoor landscapes for commercial buildings in order to give the benefits to the users and environment. Many researchers have mentioned about the applicable of houseplants to be planted in an indoor spaces either houses, residential and even in commercial building such as hotels and shopping complex. However, there are a lot of buildings that does not applied this indoor landscape even though they know the advantages of having the house plants especially in Malaysia. Furthermore, the awareness of the people of having indoor plant is still low as claimed by Rasuli (2013) that plants could give thousands of benefit to the human health but only some of them discovered out of these as the main disadvantage of this concept is the maintenance. As mentioned by Paul C. Pecknold(2001) houseplant usually exhibit poor growth, yellow foliage and other sickly problems. To create a pleasant and best design of indoor landscape, there are certain qualities to take into consideration like the typology of indoor plants decorations and the plant species.